The Evolution of Gender Relations in Romania after the Great War - IGNAT-COMAN, Luminița (Studia Universitatis Babeș-Bolyai Historia, 2017)
The Romanian national state was constituted shortly after the end of the Great War, in December 1918, when provinces that had previously been under foreign rule – Bessarabia, Bukovina and Transylvania – joined the Old Kingdom of Romania. The paper focuses on the changes that occurred in the role of Transylvanian women within the new national state after 1918. I analyse their political grievances and how they acted to obtain rights by starting from the questions: Were women considered second-class citizens? How were they perceived and how did they perceive themselves? My analysis focuses on aspects such as their level of education, given that many of them had only primary school education, their career outside home, most often as domestic servants, their political rights, especially the right to vote given that the 1918 Union Declaration of Alba Iulia proclaimed universal suffrage which was later conspicuously absent from the 1923 Constitution. The article also discusses to what degree we can speak of the existence of women leaders in this period, marriage age, and the changing vision on motherhood previously seen as an obstacle to professional success. A significant part will be devoted to the arguments that women used to obtain the rights they demanded. As for sources, I mainly use newspapers in my analysis, but also legislation and political literature from the period. The article concludes that despite significant steps forward, the striking and persisting differences between women from the rural and urban areas prevented the attainment of West-European emancipation levels. The paper reveals many common features with the newly-formed nation states that took a similar path. Therefore, the paper is a historical and a comparative analysis of feminism as an important factor for gender relation changes after the Great War. Rezumat: Evoluția relațiilor de gen în România după primul război mondial. Statul român s-a constituit la sfârșitul primului război mondial, în decembrie 1918, când provinciile aflate anterior sub dominație străină - Basarabia, Bucovina și Transilvania - s-au alăturat Vechiului Regat al României. Articolul de față se focalizează pe schimbările care au loc în ceea ce privește rolul femeii în cadrul noului stat, după 1918. Voi analiza nemulțumirile lor politice și modul în care au acționat pentru a obține drepturi pornind de la întrebările: au fost considerate femeile cetățeni de rang doi? Cum au fost percepute și cum s-au autoperceput? Analiza se concentrează pe aspecte ca: nivelul de educație, dat fiind faptul că multe dintre ele aveau doar școala primară, cariera lor, cel mai adesea ca servitoare, drepturile lor politice în special dreptul de vot, având în vedere faptul că Declarația de la Alba Iulia proclama sufragiul universal care a fost apoi cu desăvârșire absent din Constituția adoptată la 1923. Articolul discută, de asemenea, în ce măsură putem vorbi despre existența unor femei-lider în această perioadă, vârsta la căsătorie și schimbarea viziunii asupra maternității, văzută anterior ca o piedică în calea succesului profesional. O parte semnificativă va fi dedicată argumentelor utilizate de femei pentru a obține drepturile solicitate. În ceea ce privește sursele, voi utiliza presa și, de asemenea, legislația și literatura politică a perioadei. Articolul concluzionează că, în pofida unor progrese semnificative, diferențele izbitoare și persistente dintre femeile din zonele rurale și cele urbane au împiedicat atingerea nivelurilor de emancipare vest-europene. Lucrarea relevă trăsături comune cu statele națiunilor nou formate, care au avut un parcurs similar. Prin urmare, lucrarea este o analiză istorică și comparativă a feminismului ca un factor important pentru schimbarea relațiilor de gen după primul război. Cuvinte-cheie: femei, război, Transilvania, România, drepturi.